Utilization of therapeutic plasma exchange for hyperbilirubinemia in a premature newborn on extracorporeal membrane oxygenation. Issue 5 (6th May 2019) - Belousova, Tatiana; Tong, Yi; Bai, Yu; Klein, Kimberly; Tint, Hlaing; Castillo, Brian
Abstract: BACKGROUND: We report a case of a premature newborn girl with a hospital course complicated by suspected respiratory syncytial virus pneumonitis for which she was placed on veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO). Despite phototherapy, her total bilirubin steadily increased to a peak of 50.4 mg/dL with concern for bilirubin‐induced neurologic dysfunction, kernicterus. STUDY DESIGN AND METHODS: Therapeutic plasma exchange (TPE) was achieved via connection with the VA‐ECMO circuit. Our institution's standard apheresis procedural parameters were adjusted to account for the small body weight and thus the low blood volume of the neonate while on ECMO. These included calculating the total blood volume to include the patient as well as the ECMO circuit, priming of the apheresis instrument with packed red blood cells to limit the extracorporeal volume, using a lower inlet flow rate, the connection setup of the inlet and return line, and monitoring of ionized calcium and anticoagulation throughout the procedure. RESULTS: A total of three TPE procedures were performed over three consecutive days. This resulted in improvement and stabilization of the patient's bilirubin. CONCLUSION: This case emphasizes that TPE is feasible on a neonate with a suboptimal body weight and thus a low blood volume due to the increased blood volume provided while on ECMO. In the absence of ECMO, whole blood manual exchange transfusion is recommended as TPE would be unsafe due to significant extracorporeal volume that would occur during TPE in a pediatric patient with low body weight.